About natural signs in tourism, the challenges of their interpretation, and symbols determining the rules of conduct after the occurrence of selected phenomena - Kapusta, Armina (Who needs tourism?, 2024)
The article aims to analyze an issue in tourism semiotics – the interpretation of selected natural signs that travelers may encounter during their journeys. In many cases, tourists fail to react appropriately to natural signs, even those indicating health or life-threatening hazards. They have not got into the habit of reading signs that inform them about risks and guidelines for dealing with them. Due to the sense of carefreeness during vacations, tourists often passively await a reaction from tourism organizers, who then face the challenge of taking actions tailored to the different abilities of tourists to interpret signs, as well as the lack of standardization of some associated symbols. The selection of signs for analysis is subjective, based on observations made during tourist trips, work with tourists and tourism students. It also relates to current issues as climate change.